Recent Advancement in Nanotechnology for the Treatment of Pharmaceutical Wastewater: Sources, Toxicity, and Remediation Technology - Kumar, Sandeep; Yadav, Sangita; Kataria, Navish; Chauhan, Amit Kumar; Joshi, Seema; Gupta, Renuka; Kumar, Parmod; Chong, Jun Wei Roy; Khoo, Kuan Shiong; Show, Pau Loke (Current pollution reports, 2023)
The textile, paper and pulp, distillery, and pharmaceutical industries are only a few of the many sectors that contribute significantly to the contamination of water bodies and their unsuitability for human use. Pharmaceuticals, which are credited with saving millions of lives in recent decades, have emerged as a new category of environmental hazard. Their prolonged presence in the environment has a number of negative effects, including gene toxicity, hormone interference, antibiotic resistance, the imposition of sex organs, and many others. To ensure that everyone in the world can access to uncontaminated and safe drinking water, it is important to treat pharmaceutical laden wastewater before discharge in fresh water body. Nanotechnology is getting significant attention due to enormous properties such as the high surface area to volume ratio, new optical properties, and desired shape. Nanomaterials might be a strong option for purifying water of a variety of environmental pollutants. This review also touches on several environmental aspects of pharmaceuticals, including (i) the current status of pharmaceuticals production and their use pattern, (ii) sources, occurrence, and transport behaviour of pharmaceuticals, (iii) analysis techniques and potential toxicity of pharmaceuticals and (iv) various conventional and advanced nanotechnology for water remediation. The present review is predominately designed to highlight the progress and major update in advantaged nanotechnology for remediation of pharmaceutical contaminated wastewater. The literature study (2015–2022) critically illustrated the recent pharmaceutical contaminations concerns and remediation efforts emphasizing nanotechnology like nanoadsorption, AOPs, nano-catalyst, electrochemical degradation and nanomembrane/nanofiltration technology.